Analisis Kemampuan Pelafalan Kosa Kata Bahasa Arab pada Siswa Kelas VIII Madrasah Tsanawiyah (MTs) Al-Inayah - Latifah Salsabilah (Al-Mazaya: Jurnal Pendidikan Bahasa Arab, 2024)
Language is very important for us to learn, as is how to pronounce it. In every language there are certain rules and patterns in pronunciation that must be followed in order to be understood well, this is the same with Arabic. Therefore, this research aims to determine the pronunciation ability of Arabic vocabulary in class VIII MTS Al Inayah students. This research was conducted at MTS Al Inayah Bandung City (Cijerokaso Street No.63 RT 07/RW 01, Sarijadi, Sukasari District, Bandung City, West Java), specifically class VIII. The research method we use is a qualitative method. Namely by collecting data directly using an interview system in the form of a one-by-one oral test, to see how fluent the student's ability to pronounce Arabic vocabulary is. This research reveals that the majority of students show great ability in pronunciation of Arabic vocabulary, variations in this ability can be related to the background of previous experience, the intensity of learning Arabic, and the level of student dedication to the lesson material. The analysis shows that students who are consistently involved in pronunciation practice have a better tendency to master Arabic pronunciation skills